Construction supervision - Rounds, Jerald L. (RSMeans., 2011)
"This book covers all supervisory situations one is likely to encounter on a commercial, industrial, or institutional construction project. The book is based upon a very successful Electrical Project Supervision (EPS) training program developed by Rounds and Segner for the National Electrical Contractor?s Association and licensed to several organizations representing other construction sectors. This program has been delivered for over a decade and continues to be delivered to thousands of construction supervisors each year. The program content has consistently received outstanding reviews and evaluations in numerous different venues"--